Giant Piezoelectricity of Ternary Perovskite Ceramics at High Temperatures. (22nd January 2019) - Zhao, Tian‐Long; Bokov, Alexei A.; Wu, Jingen; Wang, Hongli; Wang, Chun‐Ming; Yu, Yang; Wang, Chun‐Lei; Zeng, Kaiyang; Ye, Zuo‐Guang; Dong, Shuxiang
Abstract: Here, novel ferroelectric ceramics of (0.95 − x )BiScO3 ‐ x PbTiO3 ‐0.05Pb(Sn1/3 Nb2/3 )O3 (BS‐ x PT‐PSN) of complex perovskite structure are reported with compositions near the morphotropic phase boundary (MPB), and which exhibit a piezoelectric coefficient d 33 = 555 pC N −1, a large‐signal coefficient d 33 ∗ ≈ 1200 pm V −1 at room temperature, and a high Curie temperature T C of 408 °C. More interestingly, this ternary system exhibits a giant and stable piezoelectric response at 200 °C with a large‐signal d 33 ∗ ≈ 2500 pm V −1, matching that of the costly relaxor‐based piezoelectric single crystals at room temperature. The mechanisms of such giant piezoelectricity and its characteristic temperature dependence are attributed to the spontaneous polarization rotation and extension under an electric field and the MPB‐related phase transition. The findings reveal that the BS‐ x PT‐PSN ceramics constitute a new family of high‐performance piezoelectric materials suitable for electromechanical transducers that can be operated at high temperatures (at 200 °C, or higher). Abstract : Ferroelectric ceramics of (0.95 − x )BiScO3 ‐ x PbTiO3 ‐0.05Pb(Sn1/3 Nb2/3 )O3 exhibit a giant and stable piezoelectric response at 200 °C with a large‐signal d 33 ∗ ≈ 2500 pm V −1, which is comparable to piezoelectric single crystals. Relevant physical mechanisms underlying the temperature‐enhanced spontaneous polarization rotation and extension under an electric field is demonstrated by Landau–Ginsburg–Devonshire phenomenological model.